Serum Sclerostin, Body Composition, and Sarcopenia in Hemodialysis Patients with Diabetes. (10th February 2020) - Medeiros, Maria Carolina; Rocha, Natalia; Bandeira, Elba; Dantas, Isabel; Chaves, Conceição; Oliveira, Mario; Bandeira, Francisco
Abstract : Sclerostin (Scl) is an osteoblast-inhibiting glycoprotein that is secreted mainly by osteocytes and is regulated by hormonal changes and skeletal loading. Decreased physical function and high serum Scl concentrations have been reported in chronic renal failure patients but little is known to date about the differences between diabetic and non-diabetic patients on hemodialysis who are susceptible to both sarcopenia and bone fragility. Objective .To determine the prevalence of sarcopenia and its association with serum Scl concentrations and metabolic parameters in 92 patients on hemodialysis. Anthropometric data and physical performance were evaluated in this study. Blood samples were collected for Scl, glucose, cholesterol, triglycerides, calcium, phosphate, PTH, and 25 OH-vitamin D measurements. Lean mass was evaluated using multifrequency electro-bioimpedance after dialysis session. Results . Mean age was 63.3 ± 13.6 years, 63% of patients were male, and 44.6% had diabetes. Mean body mass index (BMI) was higher in diabetics (26.6 ± 5.2 vs. 24.1 ± 3.7; p = 0.01 ) and there were no differences in gait speed and handgrip strength between diabetic and non-diabetic subjects. A low skeletal muscle mass index (SMI) was identified in 65.2% of the participants, and among them 76.7% were men and 36.7% were diabetics. Mean serum Scl was 86.9 ± 39.0 pmol/L, which was higher in men (94.6 ± 41.7; p = 0.017 ), in those individuals with low SMI (94.9 ± 40.7; p < 0.001 ), and in diabetics (97.2 ± 46.6; p < 0.003 ). After multivariate analysis and adjustments for potential confounders, high serum Scl was independently associated with low SMI and with the presence of diabetes. The following variables correlated positively with diabetes: blood pressure; BMI; waist circumference; waist/hip ratio; plasma glucose; serum Scl; and fat mass. Conclusions . We found higher serum Scl concentrations in hemodialysis patients with diabetes and these were inversely related to muscle mass.